Impacto do tratamento odontológico sob sedação na qualidade de vida relacionada à saúde bucal de pré-escolares e suas famílias - Rodrigues, Kárita Cristina Silva (2018)
There appears to be no evidence regarding the impact of dental treatment under sedation on oral health-related quality of life (OHRQoL) among preschoolers. The aim of the present study was to determine the viability of a prospective evaluation of the impact of dental treatment under conscious sedation on OHRQoL in preschool with non-cooperative behavior and their families. The Brazilian version Early Childhood Oral Health Impact Scale (B-ECOHIS) was administered before (T0), two weeks (T1) and three months (T2) after treatment. Socio-demographic and clinical data were obtained from interviews and dental charts. The difference in B-ECOHIS scores were categorized as “improvement” or “worsening” of OHRQoL. Forty-nine children and their caregivers participated. The high response rate (84.5%). The postoperative evaluation periods seem to have been sufficient to detect improvement in the OHRQoL. In T1, reduction of scores in the section "impact on the child" (p = 0.02) and subscale "oral symptoms" (p = 0.02). In T2, reduction of the total B-ECOHIS scores (p = 0.03), the subscale "child function" (p = 0.02) and the "family impact" section (p = 0.01). In both, the improvement of the OHRQoL of the majority of the participants was observed (T1 = 53.1%, T2 = 57.1%), and an improvement was associated with the number of teeth extracted (T1 p = 0.03) and male (T2 p = 0.03). It was concluded that the prospective evaluation of the impact of treatment under sedation on the OHRQoL is feasible. There was improvement in QRSRS after dental treatment under conscious sedation.